Reduced Use of Restricted and Danger-Labeled Pesticides in Florida Fresh Market Tomato Production (1992-2004) - Mark A. Mossler (EDIS, 2005)
Pesticide use values for 2004 compared to peak usage data for the period 1992 through 2004 demonstrate a 75% reduction in the application of restricted or “Danger”-labeled insecticides in fresh market tomato. Paraquat use was reduced by 31%. Fumigant use (17% reduction) was mainly influenced by rate reduction, rather than reduction of use (1-7). This document is PI-87, one of a series of publications of the Pesticide Information Office, Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2005.